The concept of comorbidity of dyscirculatory encephalopathy and vascular optical neuropathy (literature review) - T. N. Iureva; A. A. Zaika (Acta Biomedica Scientifica, 2022)
The analysis of literature data on ischemic damage to the brain and the organ of vision was carried out in order to study etiological factors, pathogenetic processes, parallel flow and mutual influence of two nosological forms: dyscirculatory encephalopathy and vascular optic neuropathy. According to the World Health Organization, there is much more people suffering from cardiovascular diseases: atherosclerosis, hypertension, diabetes mellitus and coronary heart disease. These diseases result in ischemic damage to a number of vital organs, including the central nervous system and the visual analyzer. Chronic vascular pathology of both the brain and the eye is one of the leading causes of patients’ life quality decrease of and their disability. The “triggering” causes of brain and eye damage, according to researchers, are cerebral atherosclerosis, elevating/fluctuating blood pressure, coronary heart disease, and carbohydrate metabolism disorders. Disorders of the systemic blood supply caused by these etiological factors lead to a progressive lack of oxygen supply to organs and tissues, followed by the development of intracellular and cellular hypoxia, and an ischemic intracellular cascade of biochemical disorders leading to dysfunction and sometimes cell death.In addition to direct hypoxic-ischemic damage of the nervous and visual systems cells, endothelial dysfunction contributes to the progression of these diseases, leading to a pronounced change in the wall at the level of small vessels, a change in its reactivity and a violation of the coagulation properties of blood, and as a consequence, to a gradual accumulation of ischemic and secondary degenerative changes in brain and eye cells.Knowledge of etiological factors and patterns of development of brain and eye combined ischemic damage can allow clarifying the complex of diagnostic measures, developing preventive measures, as well as prescribe pathogenetically justified treatment of existing pathology.